A Field Study of the Effects of Rating Purpose on the Quality of Multisource Ratings - Greguras, G. J. (Institutional Knowledge at Singapore Management University, 2003)
Using a field sample of peers and subordinates, the current study employed generalizability theory to estimate sources of systematic variability associated with both developmental and administrative ratings (variance due to items, raters, etc.) and then used these values to estimate the dependability of the performance ratings under various conditions. Results indicated that the combined rater and rater-by-ratee interaction effect and the residual effect were substantially larger than the person effect for both rater sources across both purpose conditions. For subordinates, the person effect accounted for a significantly greater percentage of total variance in developmental ratings than in administrative ratings; however, no differences were observed for peer ratings as a function of rating purpose. These results suggest that subordinate ratings are of significantly better quality when made for developmental than for administrative purposes, but the same is not true for peer ratings.